The most common indications for measuring metanephrine and normetanephrine in plasma – a rational approach - Romana Marušić; Željka Dragila; Adriana Levaković; Ivan Lekić; Dubravka Mihaljević; Željko Debeljak; Tatjana Bačun (Medicinski glasnik, 2023)
Aim: To determine the most common indications for measuring metanephrine and normetanephrine in plasma by gender and age and to compare the concentrations of metanephrine and normetanephrine by indication, gender and age. Methods: The study was conducted on 224 patients whose plasma metanephrine and normetanephrine concentrations were measured at the Clinical Institute for Laboratory Diagnostics at the University Hospital Centre Osijek for one year, until 1st January 2020. Results: The most frequent indications for biochemical testing were adrenal incidentaloma, 138 (6.6 %), and symptoms of pheochromocytoma, 41 (18.3%). Metanephrine concentration was lower in females (p=0.009). No significant correlation was found between age and metanephrine concentration, while age and normetanephrine concentration were positively correlated (p=0.01). Of the 224 patients, only one patient was diagnosed with pheochromocytoma, whose indication for measurement of metanephrine and normetanephrine was adrenal incidentaloma. Conclusion: Adrenal incidentalomas and symptoms suggestive of pheochromocytoma are very common in the general population, while the incidence of pheochromocytoma is extremely low. Clear guidelines for the referral of patients for biochemical testing are needed to avoid unnecessary costs and to identify the correct diagnosis promptly
Keywords: adrenal glands; catecholamines; hypertension; paraganglioma; pheochromocytoma